Autonomic Nervous System Activity During a Speech Task - Dodo, Naomi; Hashimoto, Ryusaku (Frontiers in Neuroscience, 2019)
Previous research has reported that different coping types (active or passive) are required depending on the stress-inducing task. The aim of this study was to examine the autonomic nervous response during speech tasks that require active coping, by using Lorenz plot analysis. Thirty-one university students participated in this study (M = 21.03 years, SD = 2.27). This study included 3 phases: (1) resting phase, (2) silent reading phase, and (3) reading aloud phase. Autonomic nervous system responses were recorded in each phase. We asked participants to evaluate their subjective states (arousal, valence, and mood) after the silent reading phase and the reading aloud phase. We observed that the cardiac sympathetic index for the sympathetic nervous response was significantly higher during the reading aloud phase than during the silent reading phase. In contrast, the cardiac vagal index for the parasympathetic nervous response was significantly higher during the reading aloud phase than during the resting phase. There were no significant differences between the resting phase and the silent reading phase in both cardiac sympathetic and cardiac vagal indexes. We also observed that the degree of arousal was significantly higher after the reading aloud phase than after the silent reading phase. Our findings indicate that the psychological load during silent reading is ineffective for activating the sympathetic nervous system. The sympathetic nervous response was activated in the reading aloud phase. Also, the parasympathetic nervous response in the reading aloud phase was activated compared with the resting phase. Reading aloud is necessary to adequately activate the parasympathetic nervous system by requiring participants to respire (i.e., expiration) more than during resting and silent reading tasks. The increase in the cardiac vagal index likely stems from activating the parasympathetic nervous system during expiration. Although the speech task required participants to perform active coping, it was designed to activate both the sympathetic and parasympathetic nervous systems during expiration.